#### Answer

$-4x\sqrt {2y}$

#### Work Step by Step

$3x\sqrt {2y}-7x\sqrt {2y}=\sqrt {2y}\times(3x-7x)=\sqrt {2y}\times(-4x)=-4x\sqrt {2y}$

Published by
Brooks Cole

ISBN 10:
0-53449-636-9

ISBN 13:
978-0-53449-636-4

$-4x\sqrt {2y}$

$3x\sqrt {2y}-7x\sqrt {2y}=\sqrt {2y}\times(3x-7x)=\sqrt {2y}\times(-4x)=-4x\sqrt {2y}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.